The future of OPAC usage - Abu Hanipah, Rabiahtul Adauwiyah; Mansor, Yushiana (IIUM Press, 2011)
Understanding end-users' pattern of OPAC use IS Important in improving OPAC design. This chapter reports the findings of a survey which arrived at identifying preferred OPAC features